2021
DOI: 10.1101/2021.04.16.21255649
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

COVID-19 Vaccine Prioritisation in Japan and South Korea

Abstract: Background Due to a limited initial supply of COVID-19 vaccines, the prioritisation of individuals for vaccination is of utmost importance for public health. Here, we provide the optimal allocation strategy for COVID-19 vaccines according to age in Japan and South Korea. Methods Combining national case reports, age-specific contact matrices, and observed periods between each stages of infection (Susceptible-Exposed-Infectious-Quarantined), we constructed a compartmental model. We estimated the age-stratifi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 22 publications
0
5
0
Order By: Relevance
“…A strength of this model is that we know the diagnostic delay distribution (ie, symptom onset to Q), transmission onset distribution relative to symptom onset (ie, I given symptom onset), and latent period distribution (ie, E to I) based on the robust contact tracing study in South Korea (Table ). 13,23 We assumed that individuals who never developed symptoms (ie, Iasym) had the same latent period distribution as individuals who developed symptoms (ie, Ipresym to Isym) and the same infectious period distribution as the total infectious period of individuals who were symptomatic. 14 With this backward inference method, the remaining variable to estimate was the force of infection (ie, S to E).…”
Section: Model Constructionmentioning
confidence: 99%
“…A strength of this model is that we know the diagnostic delay distribution (ie, symptom onset to Q), transmission onset distribution relative to symptom onset (ie, I given symptom onset), and latent period distribution (ie, E to I) based on the robust contact tracing study in South Korea (Table ). 13,23 We assumed that individuals who never developed symptoms (ie, Iasym) had the same latent period distribution as individuals who developed symptoms (ie, Ipresym to Isym) and the same infectious period distribution as the total infectious period of individuals who were symptomatic. 14 With this backward inference method, the remaining variable to estimate was the force of infection (ie, S to E).…”
Section: Model Constructionmentioning
confidence: 99%
“…Their shares are high again in P5 and P6, but this overrepresentation was due to the sudden decrease in the share of elderlies that received prioritized vaccinations in those periods. Note that multiple strategies [ 46 , 47 , 48 ] can be formulated for an optimal vaccine allocation to meet specific goals such as the minimization of death rate or incidence rate. While Figure S4 and Table S4 show people in their 20s had a higher rate of infection than other age groups at the Shincheonji incident, the heatmaps in Figure 8 do not reflect this tendency due to the missing information on transmission links.…”
Section: Discussionmentioning
confidence: 99%
“…However, South Korean news media's investigative series revealed that the public did not necessarily think that the government's total mobilization and citizens' compliance with it were the main reasons for effective virus control in the country. According to weekly magazine SisaIn 's special series, the public's conscientious and voluntary participation in the health authorities' risk management played a significant role in South Korea's COVID‐19 control (Chun, 2020). Some critics also argued that “corona governance” was not simply top‐down and centralized but also involved active and subjective grassroots participation in the government's pandemic policies (Chekar & Kim, 2022; Jang, 2020).…”
Section: News Media Discoursementioning
confidence: 99%